Bioprospecting, Synergistic Antifungal and Toxicological Aspects of the Hydroxychalcones and Their Association with Azole Derivates against Candida spp. for Treating Vulvovaginal Candidiasis - Fernandes, Lígia de Souza [UNESP]; Ogasawara, Letícia Sayuri [UNESP]; Medina-Alarcón, Kaila Petronila [UNESP]; dos Santos, Kelvin Sousa [UNESP]; de Matos Silva, Samanta [UNESP]; de Assis, Letícia Ribeiro [UNESP]; Regasini, Luís Octavio [UNESP]; de Oliveira, Anselmo Gomes [UNESP]; Mendes Giannini, Maria José Soares [UNESP]; Scarpa, Maria Virginia [UNESP]; Fusco Almeida, Ana Marisa [UNESP] (MDPI, 2024)
Vulvovaginal candidiasis (VVC) remains a prevalent fungal disease, characterized by challenges, such as increased fungal resistance, side effects of current treatments, and the rising prevalence of non-albicans Candida spp. naturally more resistant. This study aimed to propose a novel therapeutic approach by investigating the antifungal properties and toxicity of 2-hydroxychalcone (2-HC) and 3′-hydroxychalcone (3′-HC), both alone and in combination with fluconazole (FCZ) and clotrimazole (CTZ). A lipid carrier (LC) was also developed to deliver these molecules. The study evaluated in vitro anti-Candida activity against five Candida species and assessed cytotoxicity in the C33-A cell line. The safety and therapeutic efficacy of in vivo were tested using an alternative animal model, Galleria mellonella. The results showed antifungal activity of 2-HC and 3′-HC, ranging from 7.8 to 31.2 as fungistatic and 15.6 to 125.0 mg/L as fungicide effect, with cell viability above 80% from a concentration of 9.3 mg/L (2-HC). Synergistic and partially synergistic interactions of these chalcones with FCZ and CTZ demonstrated significant improvement in antifungal activity, with MIC values ranging from 0.06 to 62.5 mg/L. Some combinations reduced cytotoxicity, achieving 100% cell viability in many interactions. Additionally, two LCs with suitable properties for intravaginal application were developed. These formulations demonstrated promising therapeutic efficacy and low toxicity in Galleria mellonella assays. These results suggest the potential of this approach in developing new therapies for VVC.
Keywords: Candidaspp; Galleria mellonella; hydroxychalcone; lipid carriers; toxicity; vulvovaginal candidiasis